2019
DOI: 10.1103/physrevd.100.064008
|View full text |Cite
|
Sign up to set email alerts
|

Repeated faint quasinormal bursts in extreme-mass-ratio inspiral waveforms: Evidence from frequency-domain scalar self-force calculations on generic Kerr orbits

Abstract: We report development of a code to calculate the scalar self-force on a scalar-charged particle moving on generic bound orbits in the Kerr spacetime. The scalar self-force model allows rapid development of computational techniques relevant to generic gravitational extreme-mass-ratio inspirals (EMRIs). Our frequency-domain calculations are made with arbitrary numerical precision code written in Mathematica. We extend spectral source integration techniques to the Kerr spacetime, increasing computational efficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 105 publications
2
53
0
Order By: Relevance
“…Figures 6-8 show the fitted complex frequencies and their Monte-Carlo error estimates, compared to Kerr QNM frequencies calculated by Berti, Cardoso, and Starinets [66,67]. 10 In each case the fitted frequencies agree with the calculated QNM frequencies, lending further support to the identification of wiggles with QNMs (more precisely, QNMs sampled at the observation points).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Figures 6-8 show the fitted complex frequencies and their Monte-Carlo error estimates, compared to Kerr QNM frequencies calculated by Berti, Cardoso, and Starinets [66,67]. 10 In each case the fitted frequencies agree with the calculated QNM frequencies, lending further support to the identification of wiggles with QNMs (more precisely, QNMs sampled at the observation points).…”
mentioning
confidence: 53%
“…More recently Refs. [8][9][10] of wiggles, demonstrated that wiggles' complex frequencies agree with known Kerr quasinormal-mode (QNM) frequencies, and concluded that wiggles are in fact "just" a sampling at the measurement point(s) of Kerr QNMs excited by the particle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore conjecture that it will remain small throughout the inspiral. Note that even in the case of an excitation of a quasi-normal mode leading to a gravitational wave burst [13], the difference between the actual QNMs (3.21) and the poles associated to the Dirichlet boundary condition will also exhibit the typical suppression ∼ k 2 such that we still expect a small correction. Parametrically in the high spin limit, the exact result is (3.23).…”
Section: An Examplementioning
confidence: 97%
“…Progress in gravitational self-force calculations has typically been achieved by first starting with a scalar analogy of the full gravitational problem [13] and with (quasi-)circular orbits [14] around static central black holes [15], and then progressively working to the actual gravitational case, to more general orbits and to rotating black holes. However, simplifications also occur for black holes rotating close to extremality.…”
Section: Introductionmentioning
confidence: 99%